2021
DOI: 10.3390/ani11030743
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Modulators of the Central Fatigue Development and Their Relationship with Athletic Performance in Jumper Horses

Abstract: The current study aimed to investigate whether peripheral modulators of serotoninergic function and neurohumoral factors’ changes in athletic horses during an official jumping competition, and to evaluate their relationship with the physical performance of competing horses. From 7 Italian Saddle mares (6–9 years; mean body weight 440 ± 15 kg), performing the same standardized warm-up and jumping course during an official class, heart rate (HR) was monitored throughout the competition. Rectal temperature (RT) m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
(58 reference statements)
0
22
0
Order By: Relevance
“…Some blood variables and texture IRT features change over time, especially after exercise tests. This phenomenon could be useful in detecting the need to continue exercise up to a certain level of effort during training to provide an expected conditioning response [ 2 , 5 , 12 ]. Among the examined blood biomarkers, WBC, CPK, and AST increased over multiple exercise trials.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some blood variables and texture IRT features change over time, especially after exercise tests. This phenomenon could be useful in detecting the need to continue exercise up to a certain level of effort during training to provide an expected conditioning response [ 2 , 5 , 12 ]. Among the examined blood biomarkers, WBC, CPK, and AST increased over multiple exercise trials.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise-induced fatigue results in temporary loss of strength and energy, leading to decreased capacity for physical activity and a decline in the execution of horses’ athletic skills [ 2 , 10 ]. A horse’s response to fatigue can include exercise termination or exercise continuation at a lower intensity [ 4 , 11 ], both of which significantly limit the results achieved in races [ 4 , 9 ] and the equestrian Olympic games [ 12 , 13 , 14 ]. Hence, exercise should include evaluation of horse state in order to avoid fatigue [ 2 , 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has already been shown that the horses' stress response to exercise is not only determined by the physical demands but also by their emotional state which is likely to be different in a competition situation than in a training situation (von Lewinski et al, 2013). Previous research on horses competing in an official jumping competition showed that although the highest heart rate values were recorded during and immediately after the jumping course, a rise in heart rate was already registered during the inbound to the show jumping arena indicating that the rise in heart rate is not only caused by an increase in physical activity but also reflects heightened emotional reactivity (Bazzano et al, 2016;Arfuso et al, 2021b). This suggests that a standardized course that is performed in a training situation might not reflect the internal load that is induced by a competition even if it is performed at the same level of difficulty.…”
Section: Comparison Of Non-specific and Discipline-specific Exercise ...mentioning
confidence: 99%
“…It is well established that physical exercise induces transient alterations in the horses' homeostasis that need to be restored by cardiovascular, respiratory, metabolic, and musculoskeletal adaptations (Assenza et al, 2018;Arfuso et al, 2020Arfuso et al, , 2021a). Among the parameters considered for the evaluation of athletic performance in horses, cardiovascular parameters are the most studied as they represent good indices of the fitness level and internal load (Bazzano et al, 2016;Arfuso et al, 2021b). As a matter of fact, cardiovascular evaluation is commonly performed in the equine athlete for assessment and monitoring of health, welfare and fitness.…”
Section: Introductionmentioning
confidence: 99%